THE EFFECT OF FINANCIAL LITERACY AND FAMILY ENVIRONMENT ON STUDENT’S INVESTMENT PREFERENCE (Study on Diponegoro University Undergraduate Students) - Amalia Oktarisa; Dinalestari Purbawati; Andi Wijayanto (Universitas Diponegoro, 2025)
Investment in student's environment is now an activity for students to start planning their finances for the future. However, in choosing a suitable investment instrument for students, students need to find which instruments are suitable according to their needs and risk profile. This study aims to analyze the effect of financial literacy and family environment on student’s investment preference in undergraduate students of Diponegoro University. This type of research is quantitative. The population of this study were undergraduate students of the Diponegoro University with the sample criteria of undergraduate students of Diponegoro University who have been investing in any investment instruments. Data collection in this study using the questionnaire method. Instrument testing was analyzed using validity test and reliability test. Data analysis techniques used in this study is linear regression analysis. The results showed that financial literacy and family environment each partially has a significant effect on student’s investment preference, financial literacy and family environment simultaneously had a significant effect on student’s investment preference and financial literacy influences student’s investment preference with family environment as moderating variable.